2011
DOI: 10.1007/s12012-011-9124-0
|View full text |Cite
|
Sign up to set email alerts
|

Leptin’s regulation of obesity-induced cardiac extracellular matrix remodeling

Abstract: Obesity-induced remodeling of cardiac extracellular matrix (ECM) leads to myocardial fibrosis and ultimately diastolic dysfunction. Leptin, an adipocyte hormone, is emerging as a novel mechanistic link between obesity and heart diseases. Despite the known essential role of leptin in hepatic and renal fibrosis, the in vivo effects of leptin on cardiac ECM remodeling remain unclear. Our objective was to define the role of leptin as a key mediator of pro-fibrogenic responses in the heart. In vitro administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 32 publications
1
48
0
1
Order By: Relevance
“…19 In particular, the metabolic effects of obesity resulting in dyslipidemia and insulin resistance seem to be the most likely mediators of changes in maternal cardiac function through changes in the composition and material properties of the myocardium. [19][20][21][22][23][24] This assertion is indirectly supported by a recent study demonstrating that Ϸ20% of women who previously had a normotensive FGR pregnancy had features of metabolic syndrome. 25 The endothelial dysfunction is another known mechanism of diastolic impairment 26 and could also play a role in the diastolic abnormalities seen in normotensive FGR, as well as PE pregnancies.…”
Section: Melchiorre Et Al Maternal Cardiac Function In Fgr Pregnanciesmentioning
confidence: 81%
“…19 In particular, the metabolic effects of obesity resulting in dyslipidemia and insulin resistance seem to be the most likely mediators of changes in maternal cardiac function through changes in the composition and material properties of the myocardium. [19][20][21][22][23][24] This assertion is indirectly supported by a recent study demonstrating that Ϸ20% of women who previously had a normotensive FGR pregnancy had features of metabolic syndrome. 25 The endothelial dysfunction is another known mechanism of diastolic impairment 26 and could also play a role in the diastolic abnormalities seen in normotensive FGR, as well as PE pregnancies.…”
Section: Melchiorre Et Al Maternal Cardiac Function In Fgr Pregnanciesmentioning
confidence: 81%
“…In the present study we focused on the effects of leptin on endothelial dysfunction, a major precursor and contributor of cardiovascular disease and a key feature of obesity, 1,40,49 and on cardiac fibrosis, another characteristic of the obese phenotype and major precursor to heart failure, atrial arrhythmias, and sudden cardiac death. 50,51 We reported for the first time that both leptin-mediated endothelial dysfunction 49 and leptin-associated increases in cardiac fibrotic markers 50 involve mineralocorticoid receptors activation. Indeed, mineralocorticoid receptors antagonism with spironolactone prevented the reduction in endothelium-dependent relaxation induced by chronic leptin treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, we showed that mineralocorticoid receptors antagonism prevented leptin-induced increases in the expression of collagen 1α1, collagen 3α1, and periostin, three profibrotic markers. This suggests that leptin-induced cardiac fibrosis 50,51 involves mineralocorticoid receptor-dependent mechanisms. Together these data present leptin-mediated increases in aldosterone as a detrimental mechanism for the cardiovascular system and as a major risk factor for cardiovascular disease in the obese population.…”
Section: Discussionmentioning
confidence: 99%
“…Whether fibroblast-specific effects of leptin mediate myocardial fibrosis in obesity has not been rigorously tested. However, exogenous leptin administration in ob/ob mice significantly increased myocardial collagen content promoting matrix-preserving actions (110). …”
Section: The Molecular Signals Regulating Obesity-associated Fibrosismentioning
confidence: 99%